2012
DOI: 10.1111/j.0000-0000.2011.01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Security Through Efficiency Focus—Insights From a Multiple Stakeholder Pilot Implementation

Abstract: E fficiency and security are often regarded as opposing factors in transport operations, with increased security causing decreased efficiency. The use of information technology holds the promise of enabling improved efficiency in freight transport operations and this article suggests and elaborates on the proposition that ''An increased focus on efficiency will result in improved security for carrier operations.'' The research for this article involved a literature review, the collection of empirical data thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Certain aspects of administration, such as the copying and registering of consignment notes, can be completely eliminated if information sharing and authentication is automated [32,44]. This was qualitatively confirmed by the Euridice Pilot [30].…”
Section: Benefits Of Ict For Hauliers According To Driver Activitymentioning
confidence: 92%
See 3 more Smart Citations
“…Certain aspects of administration, such as the copying and registering of consignment notes, can be completely eliminated if information sharing and authentication is automated [32,44]. This was qualitatively confirmed by the Euridice Pilot [30].…”
Section: Benefits Of Ict For Hauliers According To Driver Activitymentioning
confidence: 92%
“…The individual level benefits of ICT for other supply chain actors, such as consignor/consignees have been presented in previous research (e.g., [19,32]), but fall outside the scope of this paper. It was found that significant potential improvements to road transportation have been proposed for ICT enabled process change on the company and transportation network level through conceptual or simulation model based studies [35].…”
Section: Benefits Of Ict For Hauliers According To Driver Activitymentioning
confidence: 97%
See 2 more Smart Citations
“…Measures to improve efficiency in supply chain can be related to improve security and its idea contradicts the common assumption "either…or" (Sternberg, Nyquist, & Nilsson, 2012). A facilitated process is easier to secure and control and a secure process is easier to facilitate (Karlsson, 2005).…”
Section: Theoretical Backgroundmentioning
confidence: 99%